On the Existential Road From Regret to Heroism: Searching for Meaning in Life - Igou, Eric R.; van Tilburg, Wijnand A. P.; Kinsella, Elaine L.; Buckley, Laura K. (Frontiers in Psychology, 2018)
We investigated whether regret predicted the motivation to act heroically. In a series of studies, we examined the relationship between regret, search for meaning in life, and heroism motivation. First, Study 1 (a and b) established the link between regret and search for meaning in life, considering regret as a whole, action regret, and inaction regret. Specifically, regret correlated positively with search for meaning in life. In additional two studies, we examined whether regret predicted the heroism motivation and whether this effect would be mediated through search for meaning in life. Study 2 confirmed this hypothesis for individual differences in regret, using a correlational design. Study 3 confirmed the hypothesis for temporary experiences of regret, using an experimental design. In addition, in Study 3 we found that heroism motivation was more likely for people with high self-enhancement needs than for those with lower self-enhancement needs. We discuss the relationship between regret and heroism in light of these results and explore implications for everyday life.